ANALYSING THE ROLE OF MANAGERIAL STRATEGIES IN DETERMINING THE VISION AND MISSION OF ISLAMIC EDUCATION IN PRIMARY SCHOOLS - Syamsuri, Syamsuri; Nasution , Ahmad Husein; Sirait , Abdullah; Al-Atany, Syaiful Bahri; Nasor, Muhammad (Waniambey: Journal of Islamic Education, 2024)
This research discusses the role of managerial strategies in determining the vision and mission of Islamic education in primary schools. As an important element in the world of education, managerial strategies implemented in schools have a significant impact on the formation of the vision and mission that will be used as guidelines in the implementation of education. A clear and directed vision and mission will guide the educational process to create graduates who are not only academically competent but also have noble character in accordance with Islamic values. This research uses a qualitative approach with a descriptive method, which aims to reveal holistically how the role of principals and teachers in formulating and implementing the vision and mission of Islamic education in primary schools. Data were collected through observation, interviews and documentation involving principals, teachers and other relevant parties. The results show that the right managerial strategy, which involves analysing the internal and external environment, determines the success in formulating the vision and mission of Islamic education. In addition, the involvement of all stakeholders, including teachers, parents and the community, in the formulation of the vision and mission will strengthen the relevance and application of Islamic values in daily learning. The study also found that periodic evaluation of the formulated vision and mission is essential to ensure that the education provided remains in line with the times and the needs of the community.